Performing political reparation: Public service interpreters’ dispersed practices for social justice - Giustini, Deborah (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
This study examined the activities of spoken-language public service interpreters who are engaged in supporting social justice and marginalized communities across a variety of institutional settings in the United Kingdom. By drawing on a practice theory approach, it argues that public service interpreters’ ad-hoc social and communicative activities in and beyond interpreted encounters are practices of “dispersed activism”. Although lacking the organized and collective character that characterizes a social movement, dispersed activism can work towards changing unjust systems. Based on a dataset of qualitative interviews, the study revealed a group of public service interpreters as architects of political reparation who shape both communication interactions and their own professional conduct towards localized societal transformation in power-laden settings. In addition to conceptualizing public service interpreting activism as non-formalized equity-oriented practices, the study reveals how aiming at social justice imposes challenges on the interpreters’ emotional, bodily, and material involvement, with implications for the negotiation of norms of neutrality and non-engagement.